Pemulihan Ekonomi Masyarakat Di Masa Pandemi Melalui Usaha Ayam Goreng - Indah Kurniawati; Nugraheni Rintasari; Khusnul Hidayah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
The purpose of this program is to facilitate the community to have a business, especially in the food sector in order to restore the economy in the midst of the Covid-19 pandemic. The community service program carried out in the form of training and mentoring of fried chicken business for mothers participating in the Tinalan RT 16 RW 04 Prenggan Kotagede Yogyakarta. By opening a crispy fried chicken business which is one of the favorite foods of the DIY community, it is hoped that it has the potential to attract consumers so that it brings profits as expected and increases people's income. The methods used in this service are needs analysis and group formation, training on making crispy fried chicken ready to sell, marketing training and making simple bookkeeping and mentoring until the business runs for a month. In addition, participants are facilitated with equipment, raw materials and get recommendations for places to sell. The sales system is carried out alternately with the concept of profit sharing. The success of this activity was marked by the enthusiasm of the participants in participating in the training and the enthusiasm to open a crispy fried chicken business in groups. This program is expected for participants to have skills as small entrepreneurs by making various crispy fried chicken menus that aim to improve their standard of living by earning income and reducing unemployment problems due to the impact of the Covid 19 pandemic.